2017
DOI: 10.5812/jjm.13646
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacteria Associated with a Periodontal Disease in Thai Patients Based on Next-Generation Sequencing

Abstract: Background: Oral diseases depend on the relationship between host and various species of a bacterial community. The propagation of pathogenic bacteria within the mouth can cause periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Several ASVs are more abundant in the supragingival biofilm of periodontitis subjects, such as Tannerella forsythia, Fusobacterium nucleatum subsp. vincentii, Porphyromonas endodontalis, Campylobacter gracilis, Eikenella corrodens, Leptotrichia hongkongensis, Desulfobulbus HMT 041, and Treponema amylovorum were previously associated with periodontal pockets [1,10,42,47,[52][53][54].…”
Section: Discussionmentioning
confidence: 98%
“…Several ASVs are more abundant in the supragingival biofilm of periodontitis subjects, such as Tannerella forsythia, Fusobacterium nucleatum subsp. vincentii, Porphyromonas endodontalis, Campylobacter gracilis, Eikenella corrodens, Leptotrichia hongkongensis, Desulfobulbus HMT 041, and Treponema amylovorum were previously associated with periodontal pockets [1,10,42,47,[52][53][54].…”
Section: Discussionmentioning
confidence: 98%
“…One of the major species in this niche is P. gingivalis, which is a well-known and well-studied pathogen associated with periodontitis [20]. P. catoniae, in contrast, was isolated mostly in control subjects [21][22][23]. The genus Porphyromonas has been described in various other body sites including: lungs [11,24], gut [25][26][27], skin [28,29], stomach [10,30], vagina [31] and nose [10,32].…”
Section: The Genus Porphyromonasmentioning
confidence: 99%
“…Studies investigating the oral microbiome in periodontitis compared to healthy controls also found this contrast between P. gingivalis and POTG. P. catoniae was reported to be a member of the healthy oral microbiome, and P. gingivalis as a member of the core microbiome in case of periodontitis [20][21][22][23].…”
Section: Oral Diseasesmentioning
confidence: 99%
“…matruchotii KCTC 19325 isolated from human dental plaque to discover new antibacterial metabolites. This strain was initially discovered in 1925 and recognized as the most predominant strain in dental plaque on tooth surfaces. AntiSMASH analysis on this bacterial genome revealed that there is a BGC for lanthipeptide, the same class of molecule as cebulantin previously discovered by the bioactivity-HiTES method (Table S1). As a result, we identified imidafenacin-induced antibacterial metabolites and also found that C.…”
Section: Introductionmentioning
confidence: 75%